2020
DOI: 10.2174/1570162x18666200415123607
|View full text |Cite
|
Sign up to set email alerts
|

Shift in HIV/AIDS Epidemic and Factors Associated with False Positives for HIV Testing: A Retrospective Study from 2013 to 2018 in Xi’an, China

Abstract: Background: In China, although quite a few bold programmes have been made for HIV/AIDS, the epidemic has still shown an increasing trend. Objectives: The study was aimed to investigate the characteristics of new HIV/AIDS and the major factors of false positives (FP) for HIV testing. Methods: A retrospective review was performed in a teaching hospital in Xi’an between 2013 and 2018. The overall characteristics and trends of new HIV/AIDS were described. Moreover, the major factors of FP were determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Preoperative patients were more likely to have false positives, while patients who requested STD screening had a high rate of true positives. In addition, our findings indicated that samples from Pediatrics, Gynecology & Obstetrics, and Oncology departments exhibited higher FPRs, which were consistent with previous researches indicating an increased risk of false positives in pediatric, female, and oncology patients [ 20 , 21 ]. From previous reports, we can explain some of the reasons: some women are pregnant or have tumor; most false positive patients produce possibly some types of interfering antibodies from the immune reaction for some infectious pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…Preoperative patients were more likely to have false positives, while patients who requested STD screening had a high rate of true positives. In addition, our findings indicated that samples from Pediatrics, Gynecology & Obstetrics, and Oncology departments exhibited higher FPRs, which were consistent with previous researches indicating an increased risk of false positives in pediatric, female, and oncology patients [ 20 , 21 ]. From previous reports, we can explain some of the reasons: some women are pregnant or have tumor; most false positive patients produce possibly some types of interfering antibodies from the immune reaction for some infectious pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…Xi'an, which is the largest city in the north-western China, has more than 10 million population accounting for nearly one-third of the total population of Shaanxi Province ( 15 ). Compared with coastal and south-eastern regions of China, Xi'an has distinct geographic characteristics, cultural behaviors, and lifestyles, which have potential to affect the prevalence of myopia.…”
Section: Introductionmentioning
confidence: 99%